Pelindungan Busana Kebaya Dalam Perspektif Ekspresi Budaya Tradisional dan Warisan Budaya Bangsa - Winuriska, Winuriska (UNES Law Review, 2024)
Indonesian kebaya clothing as part of Traditional Cultural Expressions has not yet obtained certainty in Indonesian positive law. Traditional cultural expressions are essentially regulated in 3 (three) laws, including the Copyright Act, the Cultural Heritage Act and the Cultural Promotion Act. Indonesian kebaya fashion as a tangible product can basically be placed under the Copyright Law. However, difficulties arise to determine the original creator and originality of the creation considering that Indonesia as a country that has a variety of multicultural (multicultural), has grown various types and styles of kebaya clothing such as traditional kebaya, encim kebaya and modern kebaya. In an official state event, the first lady used kebaya to show the nation's identity. At that time the kebaya was declared as national clothing, when it used cloth with images of flowers using a shawl which at that time represented equality. As is known, kebaya clothing (both traditional and modern) has experienced a good development and gained appreciation from many circles, both domestic and foreign. As a result, the economy from this sector has also grown and has an impact, especially on the parties involved. This prompted the government to register kebaya clothing as the nation's cultural heritage at UNESCO, an organization under the United Nations that takes care of related fields. Unfortunately, the government faces obstacles because kebaya clothing has not been included in the list of national intangible cultural heritage. The problem is that although kebaya clothing is tangible, it falls into the category of intangible properties, so to be categorized as copyrighted objects according to the Copyright Law, there are difficulties because the original creator and originality cannot be found. Thus, kebaya clothing as a traditional cultural expression can be categorized as “heritage” and its protection is included in cultural promotion efforts. This paper uses a normative juridical research method to explain the protection of kebaya clothing from a legal perspective.